Chinese Finance in Latin America: Greener Financing? - Gallagher, Kevin P. (2012)
The enormous rise in Chinese financial lending to major infrastructure and heavy industry projects has raised concerns regarding the environment. Over the past twenty years, civil society has pushed for the inclusion of social and environmental guidelines regional and government development banks’ guidelines. As a result, multilateral and Western banks have established a set of internationally agreed upon lending practices. These practices have shaped the rise of social and environmental protection within the developing world by tying the availability of loans to these policy conditions. China has been a relatively newcomer in establishing similar environmental guidelines for its development banks. Although China has made some significant progress, China still has a ways to go to meet internationally established environmentally responsible lending practices.